Differentiating Autism Spectrum Disorder From ADHD Using the Social Communication Questionnaire. Issue 8 (June 2019) - Mouti, Anissa; Dryer, Rachel; Kohn, Michael
Objective: This study examined the ability of the Social Communication Questionnaire (SCQ) to differentiate between autism spectrum disorder (ASD), ADHD, and typically developing (TD) children.Method: Children ( M age = 11.27 years, SD age = 3.28) identified with ASD Severity Levels "1" and/or "2" ( n = 28), ADHD ( n = 44), dual diagnoses of ADHD and ASD ( n = 29), and TD ( n = 61) were assessed using the SCQ.Results: The SCQ differentiated between ASD and non-ASD groups. Children with ASD had higher total and domain scores on the SCQ than ADHD and TD children. The optimal cutoff total score of 13 was identified for differentiating between ASD and ADHD groups (area under the curve [AUC] = .96). Twenty eight of the 39 items were identified as significant in differentiating between ASD and ADHD.Conclusion: The SCQ continues to be a well-validated screening tool for ASD and is suitable for determining whether further ASD assessment is warranted in children with ADHD symptoms.